Serial casting for severe spastic cerebral palsy followed by single-event multilevel surgery - Sananta, Panji; Saputra, Tofan M.D.; Dradjat, Respati S. (International Journal of Research in Medical Sciences, 2020)
Casting has been used as an adjunct therapy in Cerebral palsy (CP) management. Serial casting is used to inhibit overactivity of plantarflexors, aiding surgical preparation. Currently, the surgical management of CP is done by Single-event multilevel surgery (SEMLS). We aim to report a successful case of adolescent CP treated with SEMLS with prior serial casting. An 18-year-old woman complained of difficulty walking on her feet. The patient used the back of her foot to walk since she was 4-year-old. The patient was premature with birth weight of 1300 grams. She had history of seizure when she was 8-months old. She was diagnosed with clubfoot due to CP. She underwent 3 serial castings in the course of 9 weeks. Serial casting followed by SEMLS could be an effective measure to treat adolescent CP.